Cultural-Value-Based Bureaucratic Reform in North Halmahera Regency - Kadir, A. Gau (UI Scholars Hub, 2015)
Researches on bureaucratic reform based on cultural value (cultural approach) are rarely found. In fact, the combining use of structural and cultural approaches in government bureaucratic reform can be expected to encourage the achievement of bureaucratic reform objectives. This study chose the location in North Halmahera Regency, where the community still uphold the cultural values as represented in its cultural symbol of